2022
DOI: 10.1002/jgh3.12833
|View full text |Cite
|
Sign up to set email alerts
|

Persistent epigenetic alterations in transcription factors after a sustained virological response in hepatocellular carcinoma

Abstract: Background and Aim The risk of hepatocellular carcinoma (HCC) persists in a condition of sustained virologic response (SVR) after hepatitis C virus (HCV) eradication. Comprehensive molecular analyses were performed to test the hypothesis that epigenetic abnormalities present after an SVR play a role in hepatocarcinogenesis. Methods Whole‐genome methylome and RNA sequencing were performed on HCV, SVR, and healthy liver tissue. Integrated analysis of the sequencing data focused on expression changes in transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Viruses can impose epigenetic changes that alter host transcription programs, thereby promoting their own propagation, and may contribute to cancer occurrence. We and others have recently shown that the altered epigenetic state associated with HCV infection persists, to some extent, even after cure following DAAs and IFN-based treatments [ 63 - 67 ]. This observation is consistent in various HCV infection models, including immortalized human liver and hepatoma cells, a human liver chimeric mouse model, and post-SVR human liver samples.…”
Section: Epigenetics and Gene Expression Scar Post Svrmentioning
confidence: 99%
See 2 more Smart Citations
“…Viruses can impose epigenetic changes that alter host transcription programs, thereby promoting their own propagation, and may contribute to cancer occurrence. We and others have recently shown that the altered epigenetic state associated with HCV infection persists, to some extent, even after cure following DAAs and IFN-based treatments [ 63 - 67 ]. This observation is consistent in various HCV infection models, including immortalized human liver and hepatoma cells, a human liver chimeric mouse model, and post-SVR human liver samples.…”
Section: Epigenetics and Gene Expression Scar Post Svrmentioning
confidence: 99%
“…Moreover, HCV was shown to persistently suppress innate immune pathways, including TLR3 activity, via epigenetic changes [ 66 ]. The effect of DNA methylation on transcription factors that regulate gene expression was also recently evaluated pre- and post-SVR, which remain dysregulated after HCV eradication [ 67 ].…”
Section: Epigenetics and Gene Expression Scar Post Svrmentioning
confidence: 99%
See 1 more Smart Citation